Effects of adding loose materials on improvement of the physical properties of sediment and growth of green plants - Yan Niu; Chao Guo; Shenglan Ye; Ying Wang; Ya Hu (Bangladesh Journal of Botany, 2023)
Effects of different loose materials on the growth of green plants in the sediment and the improvement of the physical properties of the sediment were studied in pot experiments. Two types of loose materials, vermiculite and shale, were chosen. The addition ratio of loose materials and sediment were set to 1:1, 1:2, 1:5. Results showed that, the sediment after adding vermiculite was more conducive to the growth of ryegrass, and when the addition ratio was 1:1 and 1:2, the growth conditions of ryegrass were the best. The fresh weight of ryegrass in the treatment with the ratio of vermiculite and sediment at 1:1 increased by 43.94% compared to that in pure sediment; In the treatment with the ratio of 1:2, the plant height increased the most, which was 6 cm higher than that in pure sediment; When large amount of loose materials were added, the moisture content of the sediment increased compared to the pure sediment treatment; after the addition of loose materials, the bulk density of the sediment decreased, and the addition of too large amount would easily lead to a low bulk density, which was not conducive to water and fertilizer retention; The addition of vermiculite can reduce the bottom sediment. Bangladesh J. Bot. 52(2): 487-493, 2023 (June) Special